59. CURRENT STATUS AND SOME FACTORS RELATED TO PHYSICAL ACTIVITY AMONG WORKERS AT DRAINAGE ENTERPRISE NO. 2 IN 2024 (Vietnam Journal of Community Medicine, 2025)
Introduction: The World Health Organization (WHO) recommends physical activity (PA) to enhance both physical and mental health in adults.Objective: To determine the proportion of workers at Drainage Enterprise No. 2 meeting the WHO-recommended levels of PA and to identify associated factors, using the Global Physical Activity Questionnaire (GPAQ).Methods: A cross-sectional study was conducted in 2024 among 171 workers. Factors associated with achieving the recommended PA levels were identified using logistic regression analysis. Results: A total of 90.5% of workers met the WHO-recommended PA levels. Male workers were 8.4 times more likely to meet the recommended PA levels compared to their counterparts (95% CI: 1–76.6). Workers with obesity had significantly higher odds of meeting the PA recommendations than underweight individuals (OR = 21.5, p < 0.05), and those with normal weight also had higher odds compared to underweight individuals (OR = 19.8, p < 0.05).Conclusion: It is necessary to actively implement awareness-raising programs on the benefits of PA among workers at the enterprise.
Keywords: physical activity; worker; GPAQ.